Filter‐probe diffusion imaging improves spinal cord injury outcome prediction. Issue 1 (3rd July 2018) - Skinner, Nathan P.; Lee, Seung‐Yi; Kurpad, Shekar N.; Schmit, Brian D.; Muftuler, L. Tugan; Budde, Matthew D.
Abstract : Objective: Diffusion‐weighted imaging (DWI) is a powerful tool for investigating spinal cord injury (SCI), but has limited specificity for axonal damage, which is the most predictive feature of long‐term functional outcome. In this study, a technique designed to detect acute axonal injury, filter‐probe double diffusion encoding (FP‐DDE), is compared with standard DWI for predicting long‐term functional and cellular outcomes. Methods: This study extends FP‐DDE to predict long‐term functional and histological outcomes in a rat SCI model of varying severities (n = 58). Using a 9.4T magnetic resonance imaging (MRI) system, a whole‐cord FP‐DDE spectroscopic voxel was acquired in 3 minutes at the lesion site and compared to DWI at 48 hours postinjury. Relationships with chronic (30‐day) locomotor and histological outcomes were evaluated with linear regression. Results: The FP‐DDE measure of parallel diffusivity (ADC|| ) was significantly related to chronic hind limb locomotor functional outcome ( R 2 = 0.63, p < 0.0001), and combining this measurement with acute functional scores demonstrated prognostic benefit versus functional testing alone ( p = 0.0007). Acute ADC|| measurements were also more closely related to the number of injured axons measured 30 days after the injury than standard DWI. Furthermore, acute FP‐DDE images showed a clear and easily interpretable pattern of injury that closely corresponded with chronic MRI and histology observations. Interpretation: Collectively, these results demonstrate FP‐DDE benefits from greater specificity for acute axonal damage in predicting functional and histological outcomes with rapid acquisition and fully automated analysis, improving over standard DWI. FP‐DDE is a promising technique compatible with clinical settings, with potential research and clinical applications for evaluation of spinal cord pathology. Ann Neurol 2018;83:37–50